2010
DOI: 10.1111/j.1469-0691.2009.03078.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide resistance in multidrug-resistant Mycobacterium tuberculosis isolates in Japan

Abstract: Thirty-six multidrug-resistant (MDR) Mycobacterium tuberculosis isolates collected in Japan were examined for pyrazinamide susceptibility and pyrazinamidase activity, and analysed by pncA sequencing and a hybridization-based line probe assay (LiPA), which was used to detect pncA mutations for the rapid identification of pyrazinamide-resistant isolates. Pyrazinamide resistance was found in 19 (53%) of them. All pyrazinamide-resistant isolates had no pyrazinamidase activity and at least one mutation in pncA. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
6
27
1
Order By: Relevance
“…It is also important to detect resistance to PZA and LVX in MDR tuberculosis, as the majority of MDR M. tuberculosis isolates have been reported to be resistant to either PZA or LVX in Japan (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to detect resistance to PZA and LVX in MDR tuberculosis, as the majority of MDR M. tuberculosis isolates have been reported to be resistant to either PZA or LVX in Japan (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also report synonymous or neutral mutations in PZA s isolates (2,9,14,17,23,55,58). We identified 5 possible pncA alterations not associated with a drug resistance phenotype among 138 sequenced clinical isolates, even though the considered mutation or codon has been described in the literature as being associated with PZA r : 14 Cys ¡ Gly (56), 64 Tyr ¡ Ser (29,42), 135 Thr ¡ Pro (17,40,56), 143 Ala ¡ Thr (17), and 175 Met ¡ Ile (29,31,53).…”
Section: Pyrazinamide-resistant Mycobacterium Tuberculosismentioning
confidence: 99%
“…2 Since testing is not routinely performed, the prevalence of PZA resistance is not well known; however, surveillance studies have reported prevalence of 52%-78% in treatment failure or MDR-TB cases, and 2%-10% in non-MDR-TB cases. 1,7,9,10 PZA is a pro-drug that enters bacteria by passive diffusion and is converted to its active form, pyrazinoic acid (POA), by bacterial pyrazinamidase (PZAse). 6,12,19 POA is expelled from the mycobacterium by an efflux pump, it is protonated in the acidic extracellular space, and the protonated form is then reabsorbed into the bacilli, where the proton is released.…”
Section: Introductionmentioning
confidence: 99%